Development Of Creativity As The Basis Of Innovative Activity Of A University Teacher - Yakovleva, E. V.; Denisenko, A. V.; Shaleeva, E. F.; Artemyeva, S. I.; Rodinova, N. P.; Ostroukhov, V. M.; Kalney, M. S. (Cuestiones Políticas, 2020)
There is an active search for policies and methods to improve the quality of education in the vocational studies system, with all that it represents. Pedagogical work is a special type of highly skilled mental work that has a creative character and is characterized by a high degree of tension. The work of a teacher is a conscious and appropriate activity for the training, education and development of students and of society as a whole. The objective of the research is to discuss the development of creativity based on the innovative activity of teachers. It is concluded that the teacher has a main role as an agent in the formation of professional knowledge among students. The real problems of psychology and pedagogy in the modern education system are the definition of the professional requirements for the personality of a modern teacher and the psycho-diagnosis of the level of his professional qualities. However, these questions take on a political meaning because they concern the human development of a society and must therefore also be politically debated.